2014
DOI: 10.4028/www.scientific.net/amm.492.561
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Renewable Energies Integration in an Essential Oils Extraction Process

Abstract: This paper presents an essential oil extraction process in accordance with sustainable development and environmental protection. The idea is to use vegetal plant after extraction as a source of energy for steam production and the condensation of steam containing essential oil is ensured by an air-cooled condenser. In this prospect, a biomass burner was designed and its efficiency was evaluated and compared to an electrical heating system. From the experiments it was found that biomass could supply the energy n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Nowadays, the constant technological advances and industrial needs maintain the constant search for new processes that minimize the problems associated with the extraction of essential oils or essences, with lower costs and higher yields. In this sense, it has been shown that in order to carry out the essential oil extraction process it is necessary to analyze production costs, solvent selection based on the final extract ratio, energy synergy (in reactions and separation), redistribution of flows, besides studying the intimate relationship with the availability of ethereal extract of the different vegetative species [1]. On the other hand, these percentages can be significantly affected due to the use of different solvents whose polarity ratio is variable, consequently, the extraction processes differ in their productivity results despite applying similar methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the constant technological advances and industrial needs maintain the constant search for new processes that minimize the problems associated with the extraction of essential oils or essences, with lower costs and higher yields. In this sense, it has been shown that in order to carry out the essential oil extraction process it is necessary to analyze production costs, solvent selection based on the final extract ratio, energy synergy (in reactions and separation), redistribution of flows, besides studying the intimate relationship with the availability of ethereal extract of the different vegetative species [1]. On the other hand, these percentages can be significantly affected due to the use of different solvents whose polarity ratio is variable, consequently, the extraction processes differ in their productivity results despite applying similar methodology.…”
Section: Introductionmentioning
confidence: 99%